Two views of globular cluster stars in the Galactic halo - Martell, Sarah L. (Assembling the puzzle of the milky way, 2012)
In [1] we reported the discovery in the Sloan Digital Sky Survey-II/SEGUE spectroscopic database of a small subset of halo red giants, 2.5%, with CN and CH band strengths indicative of globular-cluster-like carbon and nitrogen abundances. Because the formation of stars with unusual light-element abundances is thought to be restricted to high-density environments like globular clusters, this result has strong implications for both cluster formation processes and the assembly history of the Galactic halo. Here we discuss two efforts to expand upon that work.
Gesehen am 10.10.2018